THE EFFECT OF STORY FACE IN INCREASING THE STUDENTS’ READING COMPREHENSION OF NARATIVE TEXT OF THE TENTH GRADE AT SMK SWASTA YPIS MAJU BINJAI. - Yolla Aprilia; Ummi umara; Rabukit Damanik (STKIP Budidaya Binjai, 2021)
The objective of this study was find out whether there was an effect of using Story Face in increasing the students’ reading comprehension of narative text. The writer design in this study was quasi-experimental design by using pre-test and post-test non-equivalent control group design. This study was conducted with the tenth grade students of SMK Swasta YPIS Maju Binjai as the population of the study. The sample was taken by cluster random sampling, with 60 students as the sample of this study. The writer used class X TBSM with consist of 30 students as the experimental class and X TKJ wich consist of 30 students as the controled class.The writer used test asthe instrument of collecting data. The data collected from this study were analyzed using t-test formula. The result of this study that was a positive effect of the result students’ reading comprehension narative text after using Story Face strategy. It can be seen from the data analysis, it was found that value of t-observed (to) was higher than t-table (tt). The result from calculating the data was t- observation (to= 5,68) and t-table (tt=1,672) it means, to is higher than tt in significant levvel 5%, so the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted. in order words, using Story Face had effect on students’ reading comprehension of narative text of the tenth grade students at SMK Swasta YPIS Maju Binjai.